Successful treatment of severe monkeypox case with advanced HIV infection using plasma from smallpox‐vaccinated healthy population: A case report - Chuming Chen; Weiming Yao; Siran Huang; Ling Peng; Shiyan Feng; Weibo Wu; Yunlan Yi; Zhiqiang Cheng; Yang Yang; Yan Yang; Liuqing Yang; Hongzhou Lu; et al. (iLabmed)
Abstract Since the first reported case of monkeypox in the UK in May 2022, there has been an upward trend in monkeypox cases and a global outbreak. However, reports of severe cases are relatively limited. In this study, we report a case of severe monkeypox in a patient with HIV. The patient presented with skin lesions that started on his face and around the penis and persisted for several months. Throughout the course of the disease, he received systematic symptomatic supportive treatment, topical remedies, and special care for the rash. He also underwent cidofovir antiviral therapy and smallpox‐vaccinated healthy population‐derived plasma therapy in succession, with the condition ultimately showing improvement after plasma treatment. After more than 3 months of hospitalization, he fully recovered. To the best of our knowledge, this is the first reported use of smallpox‐vaccinated healthy population‐derived plasma in the treatment of severe monkeypox cases.